2014
DOI: 10.14260/jemds/2014/3424
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Metopic Suture in Cadaveric Skulls of Assamese People

Abstract: Metopic suture is formed due to failure of union of the two halves of the frontal bone. Usually the suture disappears by early childhood, but in some cases it persists as complete or incomplete metopic suture throughout life. A complete metopic suture extends from anterior aspect of bregma to the nasion which is known as metopism. The present study is carried out in 126 dry human cadaveric skulls collected from the Dept. INTRODUCTION:The metopic suture is a vertical suture running between the two halves of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The incidence of the persistent metopic suture, reported by previous studies, was found to be 1.8% in Lebanese, 3.3% in British, 7.5% in Northeastern Thai, 7.0 -9.7% in Brazilian, 2.0 -85.0% in Indian subpopulations, 11.5% in Nepalese, 35.0% in Nigerians, and 3.3 -75.0 % in Anatolian. The incomplete type is more commonly found than the complete type (Berry, 1975;Ajmani et al, 1983;Baaten et al, 2003;Bilodi et al, 2003;Castilho et al, 2006;Eroğlu, 2008;Hussain Saheb et al, 2010;Manalgiri et al, 2010;Yadav et al, 2010;Chandrasekaran and Shastri., 2011;Murlimanju et al, 2011;Chakravarthi and Venumadhav, 2012;da Silva et al, 2013;Nallathamby et al, 2013;Masih et al, 2013;Pilli and Sunder, 2013;Aksu et al, 2014;Khandare et al, 2014;Kumar and Rajasekar, 2014;Saikia 2014;Santhosh et al, 2014;Wadekar et al, 2014;Arumugam and Arrchana, 2015;Basha and Sugavasi, 2015;Khamanarong et al, 2015;Kumar and Rajshekar, 2015;Hemalatha and Rao, 2016;Nayakanati et al, 2016;Kundu et al, 2017. Shrestha et al, 2017Singh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the persistent metopic suture, reported by previous studies, was found to be 1.8% in Lebanese, 3.3% in British, 7.5% in Northeastern Thai, 7.0 -9.7% in Brazilian, 2.0 -85.0% in Indian subpopulations, 11.5% in Nepalese, 35.0% in Nigerians, and 3.3 -75.0 % in Anatolian. The incomplete type is more commonly found than the complete type (Berry, 1975;Ajmani et al, 1983;Baaten et al, 2003;Bilodi et al, 2003;Castilho et al, 2006;Eroğlu, 2008;Hussain Saheb et al, 2010;Manalgiri et al, 2010;Yadav et al, 2010;Chandrasekaran and Shastri., 2011;Murlimanju et al, 2011;Chakravarthi and Venumadhav, 2012;da Silva et al, 2013;Nallathamby et al, 2013;Masih et al, 2013;Pilli and Sunder, 2013;Aksu et al, 2014;Khandare et al, 2014;Kumar and Rajasekar, 2014;Saikia 2014;Santhosh et al, 2014;Wadekar et al, 2014;Arumugam and Arrchana, 2015;Basha and Sugavasi, 2015;Khamanarong et al, 2015;Kumar and Rajshekar, 2015;Hemalatha and Rao, 2016;Nayakanati et al, 2016;Kundu et al, 2017. Shrestha et al, 2017Singh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Agarwal et al (1979) noted that it was situated “almost exclusively” in the lower part of the frontal above nasion and Yadav et al (2010) reported it to be just above nasion in 95.95% (142/148) of specimens examined by them. In all other studies in which the incomplete suture has been documented, it is clearly located immediately superior to nasion in all cases (Ajmani et al, 1983; Aksu et al, 2014; Andrade et al, 2019; Burrell et al, 2016; Castilho et al, 2006; Chandrasekaran & Shastri, 2011; del Sol et al, 1989; Kumar & Rajshekar, 2015; Maneenin et al, 2013; Mangalgiri et al, 2010; Pilli & Sunder, 2013; Saikia, 2014; Santhosh et al, 2014; Surekha et al, 2016; Vinoth et al, 2014; Zanaty, 2017).…”
Section: Methodsmentioning
confidence: 99%
“… Note : Studies: 1, Ajmani et al (1983); 2, Castilho et al (2006); 3, Mangalgiri et al (2010); 4, Chandrasekaran and Shastri (2011); 5, Maneenin et al (2013); 6, Pilli and Sunder (2013); 7, Aksu et al (2014); 8, Kumar and Rajshekar (2015); 9, Saikia (2014); 10, Santhosh et al (2014); 11, Vinoth et al (2014); 12, Burrell et al (2016); 13, Surekha et al (2016); 14, Zanaty (2017); 15, Andrade et al (2019). …”
Section: Methodsmentioning
confidence: 99%